Back to Basics: Facilitating the Recognition of Micro-Credentials in Ontario PSE - Roger Pizarro Milian (Journal of Innovation in Polytechnic Education)
Support for micro-credentials has grown significantly over the past year within Ontario post-secondary education (PSE). However, significant barriers remain to their widespread recognition within the PSE system. This piece outlines the importance of ensuring the full recognition of micro-credentials across this system, including the maximization of student interest, promotion of employer recognition, as well as equity-related concerns. In addition, a set of tactics to facilitate the recognition of micro-credentials are discussed, including amendments to the Ontario Qualifications Framework, establishment of a fully transferable “common core” of micro-credentials, and the need for empirical tracking.